Antagonistic interaction between biochar and nitrogen addition on soil greenhouse gas fluxes: A global synthesis. Issue 10 (18th July 2021) - He, Yanghui; Yao, Yixian; Jia, Zhen; Chen, Xinyue; Zhou, Lingyan; Shao, Junjiong; Liu, Ruiqiang; Zhou, Guiyao; Fu, Yuling; Sun, Xiaoying; Zhou, Xuhui; Bai, Shahla Hosseini
Abstract: Both biochar and nitrogen (N) addition have been proposed for enhancing plant productivity and increasing carbon (C) sequestration. Although numerous studies have been conducted to examine responses of soil greenhouse gas (GHG) fluxes to biochar or N addition, biochar is often co‐applied with N fertilizer and the interactive effects of the two factors still remain unclear. In this study, we performed a meta‐analysis of manipulative experiments with 267 two‐factor observations to quantify the main and interactive effects of biochar and N addition on soil GHG fluxes at a global scale. Our results showed that biochar addition significantly increased soil CO2 emission by 10.1%, but decreased N2 O emission by 14.7%. Meanwhile, N addition increased both soil CO2 and N2 O emissions by 11.6% and 288%, respectively. The combination of biochar and N addition also exhibited significant positive effect on CO2 (+18.0%) and N2 O (+148%) emissions, but there were non‐significant changes in CH4 fluxes. Consequently, antagonistic interaction between biochar and N addition was observed in soil GHG fluxes and their global warming potential (GWP), except for CH4 uptake showing an additive interaction. This synthesis highlights the importance of the interactive effects between biochar and N addition, providing a quantitative basis to develop sustainable strategies toward widespread application of biochar to preserve cropping system and mitigate climate change. Abstract : Biochar is often co‐applied with N fertilizer and the interactive effects of the two factors on soil greenhouse gas fluxes still remain unclear. In this study, we performed a meta‐analysis to quantify the interactive effects of biochar combined with N addition on soil GHG fluxes at a global scale. Our results showed that biochar combined with N addition significantly increased soil CO2 and N2 O emissions, and antagonistic interaction between biochar and N addition were observed in soil GHG emissions, which indicate that biochar combined with N addition would be a good strategy for future sustainable agriculture.